Computation of three-dimensional fracture parameters at interface cracks and notches by the scaled boundary finite element method. (November 2015) - Saputra, Albert A.; Birk, Carolin; Song, Chongmin
Highlights: SBFEM is extended to analyse various types of crack in 3D problems. No singular element, excessive refinement or path-independent integral is required. No a priori knowledge on the stress asymptotic solutions is needed. The order of stress singularity is obtained directly from an eigenvalue solution. Extraction of stress intensity factors and T-stress based on their definitions. Abstract: This paper presents the computations of fracture parameters including stress intensity factors and T-stress of three-dimensional cracks and notches by the scaled boundary finite element method. The singular stress field along the crack front is approximated by a singularity at a point through a semi-analytical solution. The solution is expressed as a matrix power function which allows direct extraction of the fracture parameters based on their definitions. No singular element or asymptotic solution is required for the extraction process. The numerical examples presented which include bimaterial interface cracks and V-notches illustrate the accuracy and versatility of the proposed approach.